How does corporate governance influence the corporate SDG reporting? - Dosinta, Nina Febriana; Tyas, Farradesty Cahyaning (Accounting Department, Faculty of Business and Economics, Universitas Islam Indonesia, 2026)
This research examines corporate governance in relation reporting of Sustainable Development Goals (SDGs), with institutional ownership as a moderating variable. The sample for this empirical research comprises 71 manufacturing companies listed on the Indonesia Stock Exchange for over seven year period from 2017 to 2023, resulting in 497 observations. In addition, this research uses a content analysis method to obtain the extent of SDG reporting. The findings show that female directors and audit committees influence SDG reporting. Institutional ownership moderates the relationship between independent commissioners and SDG reporting. However, institutional ownership does not moderate the relationships between the board of commissioners, female directors, as well as audit committees and corporate SDG reporting. SDG disclosure in corporate reporting is essential for communicating and monitoring sustainable development and corporate sustainability. Furthermore, SDG disclosure helps mitigate agency problems by communicating the outcomes of SDG implementation.